The braincase of Chanaresuchus ischigualastensis (Archosauriformes) from the Late Triassic of Argentina - Trotteyn, Maria Jimena (2012)
Here, we present information regarding the braincase anatomy of Chanaresuchus ischigualastensis, from the Ischigualasto Formation (Carnian) of Argentina. The braincase is very similar to that previously described for Chanaresuchus bonapartei, but bears some differences: rostral contour of the basal tubera nearly transversely oriented in ventral view; basal tubera with rounded distal tips in ventral view; paroccipital processes with a slight distal widening in caudal view; sulcus on the caudal surface of each paroccipital process restricted to the proximal two-thirds of the latter; and parabasisphenoidal ventral surface transversely concave. A phylogenetic analysis was performed using exclusively neurocranial characters, including a few new characters, to investigate phylogenetic hypotheses suggested by the neurocranial evidence. The neurocranial data support a sister-group relationship between Chanaresuchus ischigualastensis and C. bonapartei, on the basis of the presence of an intertuberal plate with a concave border. Our analysis also suggests the monophyly of a group formed by both species of Chanaresuchus and Proterochampsa. This group was supported by one apomorphy: the paroccipital processes are elongated relative to their height, which did not show homoplasy in our results. Our results show that Doswellia is the sister group of the clade formed by these proterochampsids, supporting inclusion of the former within the Proterochampsia, and this clade is recovered as more closely related to archosaurs than to Euparkeria.